Penerapan Strategi Talking Stick dengan Media Kartu Berwarna Untuk Meningkatkan Aktivitas dan Hasil Belajar Aksara Jawa Kelas V SD Muhammadiyah 3 Ponorogo - Hakim, Lukman; Yulianasari, Melisa (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2021)
This study aims to describe the application of the Talking Stick learning strategy with colored card media as an effort to increase student activity and learning outcomes in Javanese learning with Javanese script. The research was conducted in class V SD Muhammadiyah 3 Bungkal Ponorogo, amounting to 19 students. The method used was Classroom Action Research (CAR) developed by Kurt Lewin. This research carried out in two cycles, each cycle consisting of planning, action, observation, and reflection. The results showed that the application of the Talking Stick learning strategy using colored card media increased. This can be proven by its application by the teacher in the first cycle reaching 87.5% and in the second cycle, the success reached 92.5%. In cycle, I student activity reached 82.5%, and in the cycle, II increased to 92.5%. Student learning outcomes in the first cycle showed that the percentage of completeness in the class reached 84.21% and in the second cycle it reached 94.74%. These results increased compared to the results during the pre-cycle, where students' completeness only reached 52.63%.